RNF126 is a peroxisomal fate switch enabling redifferentiation therapy in hepatocellular carcinoma - Qi Su; Yichun Yang; Jiayan Ren; Yu Zhang; Lijuan Fu; Qing Wu; Xu Han; Yanmin Zhang (Proceedings of the National Academy of Sciences, 2026)
Tumor hypoxia promotes dedifferentiation and metabolic reprogramming in hepatocellular carcinoma (HCC), undermining normal liver functions. Here, we identify the E3 ubiquitin ligase RNF126 as a hypoxia-inducible “peroxisomal fate” switch that links the hypoxic microenvironment to loss of hepatocyte differentiation. Under hypoxia, HIF-2α drives RNF126 expression, which in turn ubiquitinates the peroxisomal membrane transporter ABCD3, triggering selective peroxisome autophagy (pexophagy) and depletion of peroxisomes. This organelle loss ablates very-long-chain fatty acid β-oxidation and hydrogen peroxide detoxification, erasing key hepatocyte differentiation features. We show that genetic RNF126 ablation restores peroxisomal functions and impairs hypoxic HCC growth. Leveraging these insights, we developed a small-molecule RNF126 inhibitor, D665-1412, which selectively blocks hypoxia-induced pexophagy. D665-1412 treatment stabilizes peroxisomes, normalizes lipid metabolism, and reactivates hepatocytic differentiation markers, thereby “redifferentiating” HCC cells and suppressing tumor progression in vitro and in vivo. Our findings establish the HIF-2α–RNF126–ABCD3 axis as a driver of HCC dedifferentiation and present organelle-targeted redifferentiation therapy as a promising approach for liver cancer.